Effects of traditional and convenient edible bird's nest on spatial learning of male Sprague-Dawley rats - Haziq Kamal,; Khidhir Kamil,; Tan, Nelson Kar Wai; Abdul Latif Noor Amiruddin,; Manmeet Kaur Prithviraj Singh,; Nurul Aina Johaniff,; Nursyahirah Abdul Halim,; Azmawati Mohammed Nawi,; Chua, Kien Hui; Jaya Kumar, (Penerbit Universiti Kebangsaan Malaysia, 2021)
Consumption of edible bird’s nest (EBN) has been a common practice for the health benefits it is believed to provide. Hence, this study aimed to investigate the effects of both traditional edible bird’s nest (TEBN) and convenient edible bird’s nest (CEBN) on the spatial learning of male Sprague Dawley rats in a radial arm maze (RAM). A total of 24 male rats (270-300 g) were allocated into three groups based on diet given namely pellet only (control group), pellet mixed with TEBN (300 mg/kg) and pellet mixed with CEBN (300 mg/kg). The rats were fed with the aforementioned diet throughout the study for 42 days and exposed to RAM for spatial learning assessments which consisted of shaping (3 days), acquisition (8 days) and retention (1 day) trials. In the acquisition trials, CEBN reduced working memory error (WME) on day 5 compared to control, and day 6 compared to the TEBN group. TEBN markedly reduced reference memory error (RME) on day 1 and 8, time spent (day 3) and percentage of correct choices made (day 3) during the acquisition trials compared to CEBN. TEBN and CEBN significantly reduced WME, however, only CEBN increased RME during the retention trial. CEBN significantly affected the total entries produced in the RAM which indicated the non-specific effects of CEBN on the locomotion of the rats. Our findings suggested that TEBN may work better than CEBN in improving spatial learning considering the fact that CEBN markedly reduced the locomotion of the rats during the retention trial.